Ao-benzothiazole chromophore based liquid crystalline monomers and their polymerization for new side chain liquid crystalline polymers / Md. Rabiul Karim - Karim, Md. Rabiul (2014)

(untitled)
Azo-benzothiazole chromophore based new polymerizable liquid crystalline (LC) monomers, M1-M10, having different terminal substituents (CH3, OCH3, OC2H5, F, Cl etc.) at the sixth position on the benzothiazole moiety were successfully synthesized via azo coupling followed by etherification and esterification reactions. The newly synthesized monomers showed good to excellent thermal stability with decomposition temperatures corresponding to 5% weight loss in the range of 280-320oC. The LC properties of the synthesized monomers were confirmed via DSC and POM. Monomers (M1, M5 and M6) bearing H, F and Cl at the sixth position on the benzothiazole moiety revealed only smectic phase whereas CH3, OCH3 and OC2H5 substituted monomers (M2, M3 and M4) showed both nematic and smectic phases. On the other hand, monomer M7 (without terminal substitution) exhibited both nematic and smectic phases while monomers M8-M10 (CH3, OCH3 and OC2H5 substituted) showed only nematic phase. The mesophase formation as well as the mesophase stability of monomers M1-M10 was greatly influenced by the terminal substituents and the length of the mesogen. New side chain liquid crystalline polymers (SCLCPs), P1-P10, bearing azo-benzothiazole mesogen were prepared via conventional free radical polymerization from the synthesized LC monomers, M1-M10. Thermogravimetric analysis revealed that the SCLCPs, P1-P10, exhibited excellent thermal stability with decomposition temperatures corresponding to 5% weight loss in the range of 310-340oC. All the prepared polymers exhibited LC properties and the mesophase formation as well as mesophase length of the polymers were significantly influenced by the terminal substituents. The glass transition temperatures (Tg) of the polymers P1-P10 as determined by DSC were in the range of 134-81oC and these values were shifted toward v lower temperature region with the incorporation of short terminal tails in mesogenic side chain. The UV-vis absorption studies revealed that the absorption maxima (λmax) of the P1-P10 were red shifted with the incorporation of electron donating/pushing terminal substituents located in the side chain of polymers. The photoluminescence studies showed that the polymers P1-P6 exhibited blue emission whereas the polymers P7-P10 exhibited green emission. The highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) energy levels of the SCLCPs, P1-P10, were in the range of -4.80 to - 6.16 eV and -2.14 to -3.53 eV respectively. Polymer having terminal fluorine atom (P5) exhibited the lowest HOMO value of -6.16 eV among all the studied polymers. The extent of linear viscoelastic and the dynamic viscoelastic behaviours of the SCLCPs were investigated by rheology using selected polymers, P1, P3 and P4. All the polymers showed linear viscoelastic region at small and medium strain amplitudes, while non-linearity is observed at high strain amplitude. Smectic polymer P1 failed to follow the typical terminal behaviour (G ∝ ω2 and G ∝ ω) as shown by homogeneous polymeric system; instead, it exhibited gel-like behaviour in the terminal region which is characteristics of smectic polymers. SCLCPs P3 and P4 also deviated from the typical terminal behaviour due to the low molecular weight and high polydispersity of the polymers.